EVALUASI KINERJA KEUANGAN DAN TINGKAT KESEJAHTERAAN MASYARAKAT PADA PEMERINTAHAN KABUPATEN BENGKALIS - Nirwana, Ema; Taufik, Taufeni; Ratnawati, Vince (SOROT, 2014)
This study aims to determine 1) the significance ofdifferences in the average financial performance of the DistrictGovernment of Bengkalis first period and second period, and 2) thesignificance of differences in the average well-being of communities inthe District Bengkalis in first period and second period. The researchwas conducted in the District Bengkalis, using secondary data, theanalytical techniques used are independent samplet-test of variablefinancial performance include : a) self-sufficiency ratio, b)effectiveness of local own-source revenue ratio, c) efficiencyexpenditure ratio, d) the ratio of expenditure harmony of and welfareof the community include an indicator variable a) HumanDevelopment Index (HDI), b) longevity, c) mean of years schooling,d) number of literacy, and e) decent live. The result of the financialperformance of the variable regions showed that : 1) self-sufficiencyratio was significant between period I and period II. 2) effectivenessof local own-source revenue ratio, efficiency expenditure ratio, theratio harmony of state apparatus expenditure and indirectexpenditure, the ratio harmony of public services expenditure anddirect expenditure was not significant between period I and period II.While the result of research on welfare variable showed that HumanDevelopment Index, longevity, mean years schooling, the number ofliteracy, and decent live was significant between period I and periodII.